THE IMPACT OF POST-BRENNAN'S STRATEGY ON THE PIVOTAL THINKING OF MIDDLE SCHOOL STUDENTS IN MATHEMATICS - Sohaib Shaban Ismael Hamza Al_Halboosi; Mahdi Saleh Hamza Majeed Al_Masoudi (Scholars Digest Publishing, 2024)
The current research aims to study the effect of the Post and Brennan strategy on pivotal thinking among middle school students in mathematics. The researchers adopted the experimental method, as they used an experimental design with a post-test for pivotal thinking for the two independent research groups (experimental and control). The experiment was applied to a sample consisting of Of (60) students distributed equally between the two research groups, experimental group (A) and control group (B), from the fifth scientific grade students in (Abu Jaafar Al-Mansour Preparatory School for Boys) affiliated with the General Directorate in Anbar Governorate - Fallujah Education Department for the academic year (2023-2024), The researchers conducted equivalence between the experimental and control research groups with some variables, namely: previous achievement in mathematics, intelligence test, previous knowledge, and the pivotal thinking test was constructed, which consisted of (42) objective items with four alternatives, one of which represented the correct choice, as the researchers verified its validity. Its stability was found acceptable. After completing the experiment, the pivotal thinking test was applied using the statistical package (SPSS-26). Levene’s test and the t-test were adopted for two independent samples. The results showed that the students of the experimental group who were taught according to the Post and Brennan strategy outperformed the students of the control group who were taught Teaching them according to the traditional method.